Incentivising Safe Sex : A Randomised Trial of Conditional Cash Transfers for HIV and Sexually Transmitted Infection Prevention in Rural Tanzania - de Walque, Damien; Dow, William H.; Nathan, Rose; Abdul, Ramadhani; Abilahi, Faraji; Gong, Erick; Isdahl, Zachary; Jamison, Julian; Jullu, Boniphace; Krishnan, Suneeta; Majura, Albert; Migue, Edward; et al. (2012)
Objective The authors evaluated the use of conditional cash transfers as an HIV and sexually transmitted infection prevention strategy to incentivise safe sex.